Family fuctioning and health-related quality of life among adolescents of low socio-economic status. - El-Bagiz, Seilen Syahirah; Kinanthi, Melok Roro (Indigenous, 2022)
Abstract. Lower level of health-related quality of life has the potential to be experienced by adolescents with low socioeconomic status. This condition can hamper the productivity of adolescents who will enter their productive age. For this reason, it is important to strive the enhancement of health-related quality of life among adolescents with low socioeconomic status, especially by involving the family as adolescents’microsystem. This research is important as an effort to collect empirical information that can be used in improving the health related quality of life in adolescents with low socio-economic status. We hypothesized that a functional family can help adolescents with low socioeconomic status achieve a better health-related quality of life. The purpose of this study was to determine whether the dimensions of family functioningsimultaneously have significant contribution in the health-related quality of life among adolescents from low socioeconomic status background. One hundred and nine adolescents with low socioeconomic status who live in East Kalimantan province were involved as participants in this study. Convenience sampling technique was used to select participants. Self Report Family Inventory Version II (Beavers and Hampson)was used to measure dimensions of family functioning variable. KIDSCREEN 27 (Ravens-Sieberer) was used to measure health-related quality of life variable. The data in this study were analyzed by multiple regression test. The research findings showed that simultaneously dimensions of family functioning has positive and significant contribution to health-related quality of life as perceived by participants (F= 8,320; sig p= 0.000), with total contribution 28.8%. This is shows that family strength-based approach should be added in developing intervention to enhance health-related quality of life in adolescents with low socioeconomic status. Keywords: adolescence; family functioning; health related quality of life; low social economic status.